Feasibility of Using Participant Owned Smartphone Features to Conduct Ecological Momentary Assessment of Planned Exercise Behavior in College-Aged Adults - Lucas F Sheridan; Lindsay Toth; Kelley Strohacker (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2019)
Background: Ecological Momentary Assessment (EMA) allows input of affective, social, and behavioral factors by participants in real time, which reduces recall bias. While such data may help predict exercise behavior, one limitation is the need for additional devices (palm pilot) or the creation of an app for a smartphone. The use of an online survey distribution platform compatible with personal smartphones to conduct EMA of exercise behavior in free-living adults is still unclear. Methods: Across 14 days, texts with a survey link were distributed at 9:30 am, 1:30 pm, 5:30 pm, and 9:30 pm. The survey assessed hypothesized antecedents of exercise and allowed participants to log exercise behaviors. Feasibility outcomes were assessed using R. Results: From 6/13/16 to 10/26/16 recruitment yielded 29 (55% women, 24±6 years) participants. Out of 1624 prompts sent, 83.1% of the surveys were in compliance with research guidelines (i.e. completed within 60-min of receipt). On average it took 5.07±8.65-min to finish the surveys once they were started, with the average survey completed within 16.56±15.04-min from the time it was sent. Conclusions: Using Qualtrics for EMA has potential to minimize participant and administrative burden. Further feasibility testing in the general adult population is warranted.
Keywords: Short Message System; Text message prompts; Internet survey; time-series data collection; accelerometry